The effect of medical waste management on k3 employees at pratama hospital north Nias regency - Gulo, Boby Marthin; Gea, Jeliswan B.I.J; Hulu, Protection F.; Harefa, Idarni (Junal Ilmu Manajemen, 2024)
This study aims to analyze the Effect of Medical Waste Management on Occupational Safety and Health, this study uses 2 variables, namely Medical Waste Management and Occupational Safety and Health of North Nias Regency Primary Hospital Employees. The type of research used in this study is descriptive with a Quantitative approach, from the research findings, it can be concluded that Medical Waste Management can explain Occupational Safety and Health by 0.652 with a percentage of 65% of the calculation results of the T Test that T calculate the table > T is 7,932 > 2.034 and a significant value of 0.000 < 0.05, it can be said that Medical Waste Management has a positive and significant effect on K3. It is expected to improve Medical Waste Management Procedures regularly and provide innovations to all aspects of Employee Safety and Health guarantors. in order to improve employee compliance in carrying out their tupoksinya in accordance with applicable procedures and employees are more concerned about the importance of occupational safety and health.